Waging peace, building a world in which life matters : festschrift to honour Gabriele Dietrich - Dietrich, Gabriele; Ralte, Lalrinawmi; Faria, Stella; Indian Women in Theology (Bangalore, India); I.S.P.C.K. (Organization) ([New Delhi] : IWIT/ISPCK, 2004)
Festschrift in honour of Gabriele Dietrich of Tamil Nadu Theological Seminary, social activist and feminist; contributed articles on diverse aspects predominantly on social status of women and feminism in India.
Includes bibliographical references.
Keywords: Women -- India -- Social conditions; Feminism -- India